Eiszeit—Tankred Dorst’s Hamsun: “Alt, Taub und Tot” - Conner, Thomas (Nordlit, 2011)
In this paper I will take a closer look at Tankred Dorst’s play and show how it uses well-known motifs from the Hamsun legend and weaves them together to create a provocative new image of him.